Relationship between Periodontal Disease Index and Low Birth Weight Babies in Pregnant Women with Periodontitis - Ira Komara; Soertini E Lambri; Ina Hendiani (International Journal of Integrated Health Sciences, 2016)
Objective: To identify the relationship between periodontitis in pregnant women through the periodontal disease index (PDI) and low birth weight babies.Methods: A case-control study was conducted to determine the relationship between periodontitis in pregnant women through the periodontal disease index (PDI) and the low birth weight babies (LBW). The participants were mothers with periodontitis and non-periodontitis mothers aged 20–35 years who gave birth in the Department of Obstetrics and Gynecology-Dr. Hasan Sadikin General Hospital, Bandung in the period of December to January 2005. Results: Based on the chisquare test results a highly significant relationship between periodontitis and low birth weight (p=0.002) was found. The Odd’s ratio showed that the risk of low birth weight in pregnant women with periodontitis was 15.58 times higher compared to those who did not suffer from periodontitis. The periodontal disease index has an accuracy of 88.6% in predicting the incidence of LBW. It strongly influenced the incidence of LBW with a high Odd’s ratio of 28.0. Pregnant women who suffer from periodontitis with a PDI > 3.25, have 19.2 times higher risk for delivering babies with LBW compared to the non-periodontitis mothers. Conclusions: The loss of attachment affects the possibility of delivering LBW babies.Keywords: Periodontitis, periodontal disease index, low birth weight DOI: 10.15850/ijihs.v4n1.681